Evaluation of Benthic Fish Communities in the Clinch and Duck rivers as Habitat Indicators for the Endangered Pygmy Madtom, Noturus stanauli - William G Wells; Hayden T Mattingly (Southeastern Fishes Council Proceedings, 2020)
Identifying which species are associated with a specific endangered species can inform conservation managers about potential community associations and novel localities. The benthic fish community associated with the Pygmy Madtom (Noturus stanauli) in the Duck River has been documented through Index of Biotic Integrity (IBI) work at sites where the Pygmy Madtom has occurred by the Tennessee Valley Authority (TVA). To complement the Duck River data, we gathered benthic fish community data associated with the Pygmy Madtom in the Clinch River. We used Pflieger’s metrics of constancy and fidelity to evaluate fish associations with the Pygmy Madtom. We also used and adapted Pflieger’s approach to create a faunal index that will recognize potential Pygmy Madtom habitat. In the Clinch River, Mountain Madtom (Noturus eleutherus) and Golden Darter (Nothonotus denoncourti) had a constancy percentage of 100%, while the remaining associated species were each 60% or less. Bluebreast Darter (Nothonotus camurus) (50%) and Golden Darter (45.5%) had the most realistic fidelity to the Pygmy Madtom. The overall range of values for the resulting Pygmy Madtom Clinch River faunal index was -2 to 1, and Pygmy Madtom events only occurred at faunal index values of 0 to 1. In the Duck River, Banded Sculpin (Cottus carolinae), Duck Darter (Etheostoma planasaxatile), Logperch (Percina carpodes), Mountain Madtom, Redline Darter (Nothonotus rufilineatus), and Gilt Darter (Percina evides) had a constancy percentage of 100%, while the remaining associated species were at 80% or less. The Bluebreast Darter (100%) and Fringed Darter (Etheostoma crossopterum) (66.6%) had the strongest fidelity to the Pygmy Madtom in the Duck River. The overall range of values for Pygmy Madtom Duck River faunal index was -3 to 4 and Pygmy Madtom events only occurred at faunal index values from 1 to 4. The simplicity and usefulness of the Pygmy Madtom faunal indices for the Clinch and Duck rivers represent a valuable tool that field biologists and others could use to help identify additional sites potentially suitable for Pygmy madtoms throughout both rivers.
Keywords: Constancy; Fidelity; Faunal index; Pflieger